2021
DOI: 10.1136/bmjmilitary-2020-001702
|View full text |Cite
|
Sign up to set email alerts
|

Perceived hazardous physical work environments and job-related affective well-being of navy officers aboard the Republic of Korea Navy ships and submarines in South Korea

Abstract: IntroductionNavy ships and submarines are important military measures that protect the Republic of Korea. They also comprise naval officers’ workplace. However, few studies have examined naval officers’ working environment and their job-related well-being. This study aimed to explore exposure to hazardous work environments among navy officers aboard ships and submarines and their association with job-related affective well-being.MethodsThis was a cross-sectional descriptive study. The sample comprised 146 offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…self-harm, suicidal ideation) [ 24 ], depression [ 25 , 26 ], stress [ 27 ], sleepiness [ 7 ], distress [ 28 ], work-related burnout [ 29 ] and mental fatigue [ 30 ] than older staff, whilst psychological capital (defined as a set of resources including self-efficacy, optimism, hope and resilience) appeared to increase significantly with age [ 31 ]. However, Oldenburg et al [ 32 ] found that age was not significantly associated with emotional exhaustion and Jo and Koh [ 33 ] found no association between age and wellbeing. A study of Maritime Academy students found that depression and anxiety were significantly higher in students over the age of 22 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…self-harm, suicidal ideation) [ 24 ], depression [ 25 , 26 ], stress [ 27 ], sleepiness [ 7 ], distress [ 28 ], work-related burnout [ 29 ] and mental fatigue [ 30 ] than older staff, whilst psychological capital (defined as a set of resources including self-efficacy, optimism, hope and resilience) appeared to increase significantly with age [ 31 ]. However, Oldenburg et al [ 32 ] found that age was not significantly associated with emotional exhaustion and Jo and Koh [ 33 ] found no association between age and wellbeing. A study of Maritime Academy students found that depression and anxiety were significantly higher in students over the age of 22 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies considered gender as a predictor of wellbeing because most study populations were predominantly male. Gender was not found to be related to sleepiness [ 32 ] or wellbeing [ 33 ] although one study of active-duty ship-assigned military personnel found being female was associated with greater odds of screening positive for risk of depression [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations